Hyperkalemic effect of drug-drug interaction between esaxerenone and trimethoprim in patients with hypertension: a pilot study - Toshinori Hirai; Shun Ueda; Toru Ogura; Kan Katayama; Kaoru Dohi; Yuki Kondo; Yuka Sakazaki; Yoichi Ishitsuka; Takuya Iwamoto (BMC, 2024)
Abstract Background We examined whether the pharmacodynamic drug-drug interaction between esaxerenone and trimethoprim enhances the hyperkalemic effect. Methods A retrospective observational study was conducted to identify patients >18 years undertaking esaxerenone alone or esaxerenone plus trimethoprim at Mie University Hospital from May 2019 to December 2022. We performed propensity score-matching (1:1) to compare between-group differences in the maximum change in serum potassium levels (ΔK) using the Mann-Whitney U test. For esaxerenone plus trimethoprim, Spearman's correlation coefficients were used to examine correlations between ΔK and variables, including changes in blood urea nitrogen (ΔBUN), serum creatinine levels (ΔCr), and weekly trimethoprim cumulative dose. Results Out of propensity score-matched groups (n=8 each), serum potassium levels significantly increased after administration of esaxerenone alone (4.4 [4.2 to 4.7] meq/L to 5.2 [4.7 to 5.4] meq/L, p=0.008) and esaxerenone plus trimethoprim (4.2 [4.0 to 5.1] meq/L to 5.4 [4.7 to 5.5] meq/L, p=0.023). ΔK did not significantly differ between the groups (esaxerenone alone; 0.6 [0.3 to 0.9] meq/L vs. esaxerenone plus trimethoprim; 1.0 [0.4 to 1.3] meq/L, p=0.342). ΔK positively correlated with ΔBUN (r=0.988, p<0.001) or ΔCr (r=0.800, p=0.017). There was a trend of correlation of ΔK with a weekly cumulative trimethoprim dose (r=0.607, p=0.110). Conclusions The hyperkalemic effect of the drug-drug interaction between esaxerenone and trimethoprim is not notable and related to renal function and trimethoprim dosage.